The TRANSFORM DSE - an interactive decision support environment for serving smart city. Strategy development and local measure implementation. - (:unkn) unknown (My University, 2014)
The contribution deals with the decision support tool developed within the EU FP7 TRANSFORM project, a collaboration of various partners including 6 cities (Amsterdam, Copenhagen, Genova, Hamburg, Lyon and Vienna) aiming to achieve a significant progress in the transformation towards Smart Cities. The project rests on three main pillars: the development of a Transformation Agenda, designing a Decision Support Environment (DSE) and developing local measure implementation plans. The DSE is carried out by the AIT - Austrian Institute of Technology GmbH and Accenture B.V. supported by Macomi B.V. as sub-contractor of Accenture. The TRANSFORM DSE tool addresses several features: an "easy to use" interactive scenario development and result mapping, allowing selection, virtual allocation of measures and finally assessing the local and citywide effects of the measures regarding impacts on urban environment - due to energy use and greenhouse gas emissions, and on the economy - through implementation costs and effects on the cities' employment and income. The paper gives an introduction on the topic, describes the process to gather user requirements, describes the tool design regarding data base, graphical user interface and measure editor and depicts some results through screen shots. Conclusions will be made regarding the user requirement gathering process, the tool functionality requirements and an outlook discusses steps to improve the toll and extend the functionality.
Keywords: Stadtplanung; Stadtentwicklung; Energieeinsparung; Entwicklungsziel; Entscheidungsfindung; Datenerfassung; Smart City; Stadtmanagement; Steuerung; Planungsinstrument; EU-Projekt; Visualisierung